Oliver Williamson’s Opportunism - Todorova, Tamara (Theoretical and Practical Research in Economic Fields, 2026)
In his study of the modern firm Oliver Williamson proposes the concept of opportunism as the reason for vertical integration. Williamson divides opportunism conditionally into ex ante and ex post opportunism by analogy with his classification of transaction costs as ex ante transaction costs incurred prior to concluding the deal and ex post transaction costs, which arise after that. Ex ante screening can prevent ex post opportunism. Opportunism is a synonym of fraud in the market game. It is the practice of cheating, lying or stealing in business relations. It is very common in some cultures and societies which hampers prosperity and economic progress.